Separate effects of auditory and visual room size on auditorium seat preference: a virtual reality study. (December 2022) - Chen, Yuxiao; Cabrera, Densil; Alais, David
Audiovisual integrations and interactions happen everywhere, including in music concerts, where combined visual and auditory perception contributes to overall enjoyment. Thirty-three participants evaluated their overall subjective preference at various seats in four virtual auditoria, which comprised congruent and incongruent auditory and visual renders of two auditoria that differ only in size. Results show no significant difference between participants who completed the experiment in a fully calibrated and standardized laboratory environment and participants who completed remotely using various VR equipment in various environments. Both visual and auditory auditorium size have significant main effects, but no interaction. The larger hall is preferred for both conditions. Audiovisual congruency does not significantly affect preference.